If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3y = 2x + 9 Reorder the terms: 3x + 3y = 9 + 2x Solving 3x + 3y = 9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3x + -2x + 3y = 9 + 2x + -2x Combine like terms: 3x + -2x = 1x 1x + 3y = 9 + 2x + -2x Combine like terms: 2x + -2x = 0 1x + 3y = 9 + 0 1x + 3y = 9 Add '-3y' to each side of the equation. 1x + 3y + -3y = 9 + -3y Combine like terms: 3y + -3y = 0 1x + 0 = 9 + -3y 1x = 9 + -3y Divide each side by '1'. x = 9 + -3y Simplifying x = 9 + -3y
| 5/6y=5-11/12y | | 2e^4x+1=4 | | (4a-b)-(a-2b)+b= | | 7a-3a-2a-a=16 | | 7(y+3)=28 | | 3(x+7)+4=7x-4(x-4) | | xy=26 | | x^6(2x)^7/x^5 | | 50=4-(x+4) | | (x-2)-2(x+1)=x+1(x-6) | | -6a+13=-7 | | -162-3x+11x=62 | | 5x-6=5(x-8) | | -36-x+6x=29 | | 3(x-4)-4(3-x)=x+3-(x-6) | | X-0.2x=32 | | 24n+8=24n-8 | | 5(y-4)=7(2y-1) | | 2x+6+10x-5=25 | | 2x^2+7x+12=o | | 8+4(4x-6)=6-4(2x+1) | | 0.5x+0.15(70)=33.5 | | 14x+15y=100 | | -8x-34+12x=38 | | X/27=18/81 | | -5(3y+2)-10=-6(y+8)+3y | | 4(x+144444)=999999999999 | | (3X-2).5=125 | | 1.60(.2y-y)(.1-y)=y | | 4x+4=-3+2x+21 | | 0.5(x+100)=0.55x-330 | | 2x+1-4(x+1)=6x+2 |